2023
DOI: 10.1093/ofid/ofad085
|View full text |Cite
|
Sign up to set email alerts
|

A High Viral Load in Urine Correlates With Acute Kidney Injury and Poor Outcomes in Hospitalized Patients With Severe Fever With Thrombocytopenia Syndrome: A Noninvasive and Convenient Prognostic Marker

Abstract: Background Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with an extensive geographical distribution and high mortality rate. To date, the role of SFTS virus (SFTSV) in urine is still elusive. We aimed to explore the relationship between urinary bunyavirus and acute kidney injury (AKI) and mortality in patients with SFTS. Methods Urine samples were collected from 102 patients to quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(43 reference statements)
1
1
2
Order By: Relevance
“…We con rmed that U-SFTSV in SFTS patients was signi cantly associated with incidence of AKI, which is in consistent with previous reports [44]. U-SFTSV evaluation can be useful for early diagnosis of AKI in SFTS patients according to this research.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We con rmed that U-SFTSV in SFTS patients was signi cantly associated with incidence of AKI, which is in consistent with previous reports [44]. U-SFTSV evaluation can be useful for early diagnosis of AKI in SFTS patients according to this research.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that SFTSV RNA in fecal/ anal swabs of SFTS patients was associated with diarrhea incident, SFTSV RNA levels in fecal/ anal swab was dependent on virus levels in patient's blood. Acute kidney injury was con rmed as a predictive biomarker for disease severity and poor prognosis [44]. In the current study, the incidence of AKI was 39.2%, higher than previous reports [44,45].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In this research, SFTSV RNA in fecal/anal swabs of SFTS patients was found to be associated with diarrhea, SFTSV RNA levels in fecal/anal swab was dependent on virus levels in patient's blood. Acute kidney injury was confirmed as a predictive biomarker for disease severity and poor prognosis [ 44 ]. In the study, the incidence of AKI was 39.2 %, higher than previous reports [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms of AKI in patients with SFTS are unclear, some studies reported that the SFTS virus was detected in the kidneys ( Chen et al, 2012 ; Jin et al, 2012 ). Recently, a report showed that SFTS viral load in urine is an independent predictor of the incidence of AKI ( Zhang et al, 2023 ). It implies that the SFTS virus may directly induce renal damage.…”
Section: Discussionmentioning
confidence: 99%